Perception of Catholic Lessons Among the Eleventh Grade Muslim Students at SMA Santa Theresia Jakarta - Woro Retno Kris Sejati; Hatim Gazali (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
The government has regulated that each student is entitled to religious education in accordance with his/her religion. However, some schools, one of which is SMA Santa Theresia (Santa Theresia Senior High School), have special regulations. Since these schools are run by Catholic foundations, they provide Catholic religious instruction to all students. Walgito (2004) reported that a person's perception will affect a person’s actions. Therefore, this research aims to reveal the Muslim students’ perception of the Catholic lessons they follow. This research used descriptive qualitative approach. The data were collected using interviews, observation and documentation through a process of data triangulation. The subjects selected through a purposive sampling method by considering that they are the eleventh grade students and taught by the same religious education teacher. The data were analyxed using Miles and Huberman model consisting of data reduction, data display and conclusion. The results indicated that the Muslim students have positive perception of the materials that are easy to apply in their daily lives, and also have a negative perception of the materials that have a lot of memorization and theories.